2023
DOI: 10.3390/medicina59101725
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Markers in Patients with Bipolar Disorder Who Have Committed Offenses and Their Relationship with Criminal Behavior

Burcu Sırlıer Emir,
Sevler Yıldız,
Aslı Kazğan Kılıçaslan
et al.

Abstract: Background and Objectives: This study aimed to examine the function of various inflammation parameters and their interactions in the pathology of Bipolar disorder (BD) and to assess whether they could be biomarkers in the relationship between criminal behavior and BD. Materials and Methods: Overall, 1029 participants, including 343 patients with BD who have committed offenses, 343 nonoffending patients with BD, and 343 healthy controls, were included in this retrospective study. Neutrophil, lymphocyte, monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In a recent study involving 686 adults with bipolar disorder (vs. 343 healthy controls), researchers found that the systemic immune-inflammatory index (a combined measurement of neutrophils, lymphocytes, and platelet counts) was higher among people with bipolar disorder who had committed criminal offenses [187]. Similar findings of increased inflammatory immune markers have been reported for adults with schizophrenia who had committed crimes vs. noncriminal patients [188].…”
Section: Microbiome and Mechanismsmentioning
confidence: 56%
“…In a recent study involving 686 adults with bipolar disorder (vs. 343 healthy controls), researchers found that the systemic immune-inflammatory index (a combined measurement of neutrophils, lymphocytes, and platelet counts) was higher among people with bipolar disorder who had committed criminal offenses [187]. Similar findings of increased inflammatory immune markers have been reported for adults with schizophrenia who had committed crimes vs. noncriminal patients [188].…”
Section: Microbiome and Mechanismsmentioning
confidence: 56%